Product Quality, Price, and Brand Image Shaping Male Skincare Choices - Moch Rizky Khairul Rachman; Sonja Andarini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Indonesian skincare market has rapidly expanded, reflecting a lifestyle shift where skincare is essential for health and self-confidence among both men and women. Specific Background: In Surabaya, a dynamic urban center, male consumers increasingly adopt skincare routines, making brands like Kahf, a local halal-based brand, and Garnier, a global competitor, key players in this evolving market. Knowledge Gap: Despite the sector’s growth, limited research explores how product quality, price, and brand image jointly influence men’s skincare purchase decisions in Indonesia. Aims: This study examines the comparative impact of product quality, price, and brand image on the purchasing decisions of male consumers using Kahf and Garnier products in Surabaya. Results: Using a quantitative survey of 100 male respondents and multiple linear regression, findings show that all three variables collectively affect purchase decisions; however, product quality and brand image exert significant individual effects, while price is less decisive. Novelty: The research highlights contrasting brand strategies and cultural preferences shaping men’s skincare behavior, revealing Kahf’s appeal through halal authenticity and Garnier’s global credibility. Implications: These insights guide marketers to prioritize product quality and brand image to enhance consumer trust and competitive advantage in the men’s skincare market. Highlights: Product quality and brand image are the strongest drivers of purchase decisions. Price plays a minimal role compared to perceived value and reputation. Local cultural identity (Kahf) and global credibility (Garnier) shape consumer preferences. Keywords: Product Quality, Price, Brand Image, Men’s Skincare, Purchasing Decisions